A study on potential application and people awareness on green infrastructure for boulevard: a case study of Putrajaya boulevard - Mohd. Radzi, Fatin; Awang Long, Siti Sarah; Abu Bakar, Aniza (2013)
Green infrastructure is a tool in managing the environment towards achieving sustainability by integration of environmental friendly approach into the built environment. The application of green infrastructure assists to cater on the issues such as urban heat island, climate change and greenhouse effects. As the urbanization increases the paved surfaces and decreases vegetated surfaces, it leads to a reduction in evaporative cooling, thus increase the surrounding temperature. The adaptation of green infrastructure allows ecological resources such as green spaces to be maintained in order to mitigate environmental degradation. Therefore, this study focused on the application and people’s awareness of green infrastructure for the boulevard in managing energy use and climate change. Suitable green infrastructure is identified based on the characteristics of the site such as the location, function and existing physical elements. The people’s awareness and preference on the green infrastructure application were also identified. The methodology used in this study are content analysis on the characteristics of green infrastructure, observation on the existing green infrastructure and its function, a survey of 30 respondents on people’s awareness and preference. The interviews with landscape architects, planners, and engineers are conducted to identify the guidelines and principle of green infrastructure applied at the Putrajaya Boulevard. Based on the findings, eleven types of green infrastructure in managing the energy use and climate control can be applied for the boulevard. Referring to the Putrajaya Boulevard, only five types of green infrastructure are applied. Therefore, another six types of green infrastructure are suggested in managing energy use and climate change. Keywords : Green Infrastructure, boulevard, application, awareness.